PENGARUH APLIKASI BOKHASI AMPAS TAHU DAN ARANG SEKAM TERHADAP PERTUMBUHAN DAN HASIL LOMBOK (Capsicum anum L.) - Saijo Saijo (Universitas Muhammadiyah Purwokerto, 2013)
The study aimed to determine the effect of bokashi application tofu and rice husk on the growth and yield of chilli (Capsicum anum L.) Bhaskara variety. The experiment was conducted using a completely randomized design ( CRD ) factorial . The first factor is the dose bokashi application tofu ( T ) 4 levels , : T1 = 4 t ha-1 (50 g/polybag) , T2 = 6 t ha-1 (75 g / polybag ) , T3 = 8 t ha-1 (100 gram/polybag) , T4 = 10 t ha-1 ( 125 g / polybag ) . The second factor husk dose application ( A ) 4 levels , : A1 = 6.4 t ha-1 (80 g / polybag ) , A2 = 8 t ha-1 ( 100 g/polybag ) , A3 = 9.6 t ha-1 (120 g/polybag) , A4 = 11.2 t ha-1 (140 g polybag) treatment was repeated three times 48 experimental units.The results showed that the interaction of treatment administration bokashi application tofu and rice husk collectively with influential sangatnya taterhadap the meter plant height , flowering plant age , number of productive branches , the amount of fresh fruit per plant and fresh fruit weight per plant . The highest yield parameters plant height ages 20 , 30 and 40 DAS (31.00 cm , 46.90 cm and 61.77 cm) , flowering plant age and number of branches ( 19.33 HST and 14 , 00 branches ) , and the amount of fruit and fresh fruit weight per plant ( 38.67 and 69.37 g fruit ) obtained on the interaction perlaku bokashi giving tofu a dose of 10 t ha-1 ( 125 g / polybag ) and rice husk with a dose of 11.2 t ha-1 140 g/polybag (T4A4). Keyword : Bokashi pulp, rice husk and chili